LDPC code reconstruction based on algorithm of finding low weight code-words - Pei-dong YU; Hua PENG; Ke-xian GONG; Ze-liang CHEN (Tongxin xuebao)
LDPC code reconstruction without a candidate set is one of the tough problems in channel code reconstruction.First,theoretical analysis was provided for the number of received code-vectors needed for the reconstruction,and a lower bound was derived.Then,according to the lower bound,and based on an algorithm for finding low weight code-words,a new reconstruction method was proposed.It looked for low weight vectors one by one from the dual space of the received code-vector space and used them to reconstruct the sparse parity-check matrices.Number of iterations and the computational complexity of the method were analyzed based on exponential distribution theory.Under noise-free conditions,drawbacks of the existing method,including limited applicable range and large quantity of required data,have been overcame.Under noisy conditions,the proposed method has higher robustness against noise and relatively low complexity,compared to existing methods.For QC-LDPC codes,the reconstruction performance can be further improved using the quasi-cyclic property of their sparse parity-check matrices.